2016
DOI: 10.1016/j.gore.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of basal cell carcinoma of the vulva with lung metastases

Abstract: Basal cell carcinoma (BCC) is the most common non-melanomatous skin cancer, typically arising in sun-exposed areas such as the head and neck. Defective signaling through the Hedgehog (HH) signaling pathway forms the molecular basis for BCC. Surgery remains the mainstay of treatment. Basal cell carcinoma of the genital tract is rare as is metastatic BCC. We report a case of metastatic BCC in a young woman with previously resected vulval BCC presenting six years later with inguinal nodal recurrence and multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Other treatment options for superficial spreading tumors include cryosurgery and imiquimod, although tolerance of those treatments in this body area could understandably be poor. Usually, the tumor has a favorable prognosis, however metastatic vulvar BCCs have been reported [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment options for superficial spreading tumors include cryosurgery and imiquimod, although tolerance of those treatments in this body area could understandably be poor. Usually, the tumor has a favorable prognosis, however metastatic vulvar BCCs have been reported [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although the death rate from BCCs is low as BCC rarely metastasizes [ 5 , 16 ], if untreated BCC can destroy the tissues and nearby organs, causing ulceration and disfigurement. Advanced BCCs are resistant to treatment and associated with high morbidity [ 1 , 17 , 18 , 19 ]. BCC morbidity is considerable and constitutes a huge burden on the healthcare service worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Those drugs have been particularly directed against smoothened (SMO), which is an important component of the Hh pathway. Although this treatment method has been proven beneficial in many cases [ 23 , 24 ], the development of resistance remains a major concern as about 20% of patients develop resistance during the first year of treatment [ 19 , 23 , 25 ]. Studies have now shown that other pathways interact with the Hh pathway in BCC development [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher frequency of clinical recurrences and regional or distant metastasis (10 out 300 cases described) have been reported for vulvar BCCs. 2-4…”
mentioning
confidence: 99%
“…Higher frequency of clinical recurrences and regional or distant metastasis (10 out 300 cases described) have been reported for vulvar BCCs. [2][3][4] We describe 4 cases of vulvar BCCs, 3 of which were located in the inner side of the labia majora and 1 on the hairy zone of the vulva. In all these cases, we describe also the expression pattern of different cytokeratins and proliferation markers by immunohistochemistry.…”
mentioning
confidence: 99%